Hypoglychemic activity of Moringa oleifera extract in streptozotocin-induced diabetic rats - Rabiatul Adawiyah; Tri Setyawati; Rahma Badaruddin; Listawati (Acta Biochimica Indonesiana, 2024)
Background: Diabetes mellitus, particularly Type 2 (T2DM), is a global health concern characterized by high blood glucose levels and insulin resistance. Objective: This study aims to explore the hypoglycemic potential of M. oleifera, a plant that thrives in Central Sulawesi, using a rat model of T2DM. Method: Healthy male Wistar rats (weight 200-300 g, aged 9-11 weeks) were used in the experiment. The rats were divided into five groups: normal control (healthy), negative control (diabetic without treatment), positive control (diabetic treated with 9 mg/200 g metformin), treatment 1 (diabetic treated with 400 mg/kg BW M. oleifera extract), and treatment 2 (diabetic treated with 800 mg/kg BW M.oleifera extract). Fasting blood glucose levels were measured enzymatically using the Glucose GOD FS kit from DiaSys. Data were analyzed using ANOVA followed by post-hoc analysis. Results: The fasting blood glucose levels significantly differed among the groups (ANOVA, p = 0.0426). The normal control group maintained stable glucose levels (108.3 ± 8.34 mg/dL pre-test and 106.6 ± 29.67 mg/dL post-test). The negative control group showed a marked increase in glucose levels (185.3 ± 36.28 mg/dL to 268.6 ± 17.63 mg/dL). The positive control group (metformin) significantly reduced glucose levels (386.8 ± 64.22 mg/dL to 230.8 ± 25.82 mg/dL). Treatment 1 (400 mg/kg BW) reduced glucose levels from 292.2 ± 0.98 mg/dL to 218.1 ± 13.74 mg/dL, and treatment 2 (800 mg/kg BW) showed a substantial reduction from 287.3 ± 85.30 mg/dL to 145.3 ± 28.30 mg/dL. However, the Bonferroni post-hoc analysis indicated no significant differences between pre-test and post-test levels within each group. Conclusion: The M.oleifera extract exhibited a hypoglycemic effect in diabetic rats, with the higher dose (800 mg/kg BW) showing a more pronounced effect.